Exploring Ways to Improve Elementary School Statistics Education Through Analysis of Middle School Social Studies Textbooks: Focusing on Statistical Graph Teaching - Byungjoo Tak; Eun-Sung Ko (Korea Society of Educational Studies in Mathematics, 2020)
In this study, in order to explore ways that statistical graphs teaching in elementary mathematics education can be improved, first, the types of statistical graphs that appear in middle school social textbooks were examined, and second, the characteristics that differentiated these from statistical graphs that appeared in elementary school mathematics were investigated. This analysis indicated that 88.2% of the graphs presented in the middle school social textbooks were addressed in the elementary mathematics curriculum. The frequency of use (excluding mixed graphs) was in the order of bar graphs, line graphs, ratio graphs, and picture graphs. However, most of the statistical graphs did not follow the standardized framework suggested in elementary school mathematics textbooks, as they were instead transformed in various ways. The features that differentiated middle school mathematics graphs from graphs experienced in elementary school mathematics differed for each type of graph. For example, in the case of bar graphs, there were the omission of axes, deformation of bars, and expression of multiple variables, while in the case of line graphs, there were expressions of multiple variables and accurate representations of variables.